Stakeholders’ Perspectives on Banking Support and Digital Accounting Adoption in the Palm Oil Industry - Panjaitan, Harry Patuan; Renaldo, Nicholas; Junaedi, Achmad Tavip; Nyoto, Nyoto; Jahrizal, Jahrizal; Dalil, M; Arief, Dodi Sofyan; Puspita, Fifi; Nyoto, Rebecca La Volla; Veronica, Kristy (Luxury: Landscape of Business Administration, 2025)
This study aims to investigate how stakeholders, including palm oil enterprises, smallholder cooperatives, banking institutions, and regulators, perceive the role of banking support in facilitating or hindering the adoption of digital accounting systems. This study employs a qualitative exploratory design to capture the diverse perspectives of stakeholders on the role of banking support in facilitating digital accounting adoption within the palm oil industry. A purposive sampling strategy will be employed to ensure participants possess direct experience with either banking support or digital accounting adoption. Data will be analyzed using thematic analysis. Interview transcripts, focus group notes, and documents will be coded inductively and deductively, guided by the research questions. The findings reveal that banks are not merely providers of financial capital but also act as institutional gatekeepers that shape reporting practices and encourage digital transformation. Larger enterprises view digital accounting as a strategic tool for efficiency and compliance, while smallholders often see it as a burdensome requirement.